Ab initio calculation of the equilibrium positions and electronic spectra of oxygen and carbon impurities in silicon - Gorkavenko, T. V.; Plyushchay, I. V.; Makara, V. A. (Reports of the National Academy of Sciences of Ukraine, 2016)
Ab initio calculation of the equilibrium positions of oxygen and carbon impurities in a supercell composed of 64 Si atoms are presented. The density functional theory in the general gradient approximation and the software package ABINIT are used in numerical calculations. It is shown that the carbon impurity, as opposed to oxygen, can be in stable and metastable states. We have obtained that the angle of Si−O−Si quasimolecules is ∼136 ◦, and the angle of Si−C−Si quasimolecules is ∼136 ◦. The electronic spectra of a supercell composed of 64 Si atoms with oxygen and carbon impurities in different positions are presented and analyzed. The calculation results are analyzed in terms of the possible formation of the band magnetism.